The Association of TET2 Gene Polymorphisms (rs34402524 and rs2454206) and their Haplotypes with Response to Treatment in Chronic Myeloid Leukemia Patients - Ismail, Noor Hashim; Abdulhassan, Ismail Abdulridha; Al-Faisal, Abdul Hussein Moyet (Iraqi Journal of Science, 2024)
Genetic and epigenetic factors affect chronic myeloid leukemia (CML) treatment response. The aim of the present study was to investigate the association of two TET2single nucleotide polymorphisms (SNPs) (rs34402524 and rs2454206) with CML incidence and response to imatinib mesylate (IM) treatment. Blood samples were collected from fifty CML patients (25 responders and 25 non-responders) and 50 healthy controls.Genotyping of TET2 gene rs34402524and rs2454206 was done by qualitative real-time PCR-based genotyping methods. The results of the present study revealed a significant increasein risk association of TET2 rs34402524 and rs2454206 heterozygous genotypes (TG) and (AG) with CML incidence and significant increased risk association of TET2 rs34402524 heterozygous genotype (TG) with non–responsiveness to IM treatment in CML patients.This study revealed a strong linkage disequilibrium (LD) of TET2 gene rs34402524 and rs2454206 SNPs among CML patients and controls and the haplotype G-G was significantly associated with a 2.475fold increased risk for CML incidence.In conclusion, both TET2 gene SNPs (rs34402524 and rs2454206) heterozygous genotypes(TG) and (AG) associated with increased risk of CML incidence and the heterozygous genotype (TG) of TET2 gene rs34402524 SNP associated with increased risk of non –responsiveness to IM treatment in CML patients. Both studied TET2 SNPs (rs34402524 and rs2454206) could be used as markers for predicting response to imatinib in CML patients.